2013
DOI: 10.1097/fjc.0b013e318288a6d7
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy and Tolerability of Azilsartan in Mice With Left Ventricular Pressure Overload or Acute Myocardial Infarction

Abstract: Angiotensin II receptor blockers (ARBs) are used for the treatment of patients with heart failure and hypertension. Yet their safety has been questioned by some who observed delayed cardiac healing and scar thinning after myocardial infarction (MI). To clarify potential efficacy and safety of ARBs, we administered Azilsartan medoxomil, a prodrug of an ARB (Takeda Pharmaceutical Company Limited), assessed cardiac fibrosis (hydroxyproline content), left ventricular (LV) wall thickness (premortem echocardiography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Additionally, azilsartan attenuated LPS-induced inflammation and oxidative stress in U937 macrophages and lung injury through the modulation of Nr2/HO-1 pathway [39,40]. Furthermore, it showed promising activity in acute myocardial infarction [41] and exerted a potential protective effect against cisplatin-induced cytotoxicity [42]. The present study aimed to examine the effect of azilsartan on renal IR injury in rats and the possible molecular mechanisms implied this effect by inspecting apoptosis and HMGB1/NF-κB/p38/ERK1/2/JNK signaling pathways.…”
Section: Introductionmentioning
confidence: 98%
“…Additionally, azilsartan attenuated LPS-induced inflammation and oxidative stress in U937 macrophages and lung injury through the modulation of Nr2/HO-1 pathway [39,40]. Furthermore, it showed promising activity in acute myocardial infarction [41] and exerted a potential protective effect against cisplatin-induced cytotoxicity [42]. The present study aimed to examine the effect of azilsartan on renal IR injury in rats and the possible molecular mechanisms implied this effect by inspecting apoptosis and HMGB1/NF-κB/p38/ERK1/2/JNK signaling pathways.…”
Section: Introductionmentioning
confidence: 98%
“…This is consistent with previous reports of reduced hypertrophy in patients (without diabetes) treated with ARBs. 41 Thus, the decrease in hypertrophy noted in this study may have been attributable in part to reduced pressure after load secondary to suppression of activity of the RAAS. Improved cardiac function, reflected by increased CO and stroke volume, was observed as well in mice treated with azilsartan.…”
Section: Discussionmentioning
confidence: 60%
“…ACE inhibitors are standard therapy in patients with hypertension 50 and heart failure. 41 In addition, we have found that azilsartan was safe and well tolerated in normal mice subjected to aortic banding. Increased activity of RAAS in both laboratory animals 25,26 and patients 27,29 with the metabolic syndrome is well established.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation